PENGARUH MODEL PEMBELAJARAN GROUP INVESTIGATION (GI) BERBANTUAN MEDIA BOOKLET TERHADAP PEMAHAMAN KONSEP BAGUN RUANG PADA SISWA KELAS IV SDN 04 BATU AMPAR - Sinarti, Sinarti; Rif'at, Mohamad; Mutazam, Mutazam (STKIP Melawi, 2018)
Abstract: The purpose of this research was to : (1) To acknowledge geometry concept understanding on the fourth grade students at SDN 04 Batu Ampar before and after using group investigation learning model with support of booklet. (2) To acknowledge the influence of group investigation learning model with support of booklet to geometry concept understanding on the fourth grade students at SDN 04 Batu Ampar. (3) To acknowledge the influence percentage group investigation learning model with support of booklet to geometry concept understanding on the fourth grade students at SDN 04 Batu Ampar. This reseacrh was a pre experimental design, and this design is one group pretest-postest. This research did to the fourth grade students at SDN 04 Batu Ampar, there were have 22 students (13 boys and 9 girls). The result of this research : (1) The student’s geometry concept understanding before and after using group investigation learning model with support of booklet was different. (2) This research shown that there was a significant influence from group investigation with support of booklet to geometry concept understanding on the fourth grade students at SDN 04 Batu Ampar. (3) The influence of group investigation learning model with support of booklet to geometry concept understanding on the fourth grade students at SDN 04 Batu Ampar was 49,53 %. Keywords : group investigation, booklet, concept understanding, geometry. Abstrak: Penelitian ini bertujuan untuk (1) Mengetahui pemahaman konsep bangun ruang siswa kelas IV SDN 04 Batu Ampar antara sebelum dan sesudah menggunakan model pembelajaran group investigation berbantuan media booklet. (2) Mengetahui pengaruh model pembelajaran group investigation berbantuan media booklet terhadap pemahaman konsep bangun ruang siswa kelas IV SDN 04 Batu Ampar. (3) Mengetahui seberapa besar pengaruh model pembelajaran group investigation berbantuan media booklet terhadap pemahaman konsep bangun ruang siswa kelas IV SDN 04 Batu Ampar. Jenis penelitian ini adalah Pra Eksperimen (Pre Experimental Design), dengan bentuk one group pretest-postest design. Penelitian ini dilakukan terhadap siswa kelas IV SDN 04 Batu Ampar yang berjumlah 22 orang, terdiri dari 13 siswa laki-laki dan 9 siswa perempuan. Hasil penelitian (1) Pemahaman konsep siswa antara sebelum dan sesudah menggunakan model pembelajaran group investigation berbantuan media booklet adalah berbeda, (2) Terdapat pengaruh yang signifikan dari model pembelajaran group investigation berbantuan media booklet terhadap pemahaman konsep bangun ruang siswa kelas IV SDN 04 Batu Ampar, (3) Pengaruh dari model pembelajaran group investigation berbantuan media booklet terhadap pemahaman konsep bangun ruang siswa kelas IV SDN 04 Batu Ampar adalah sebesar 49,53%. Kata Kunci : group investigation, booklet, pemahaman konsep, bangun ruang.